Pengembangan Penglukatan Pancoran Solas Pura Taman Mumbul Menjadi Destinasi Wisata Religi Internasional - Sutapa, I Wayan; Sriyanti, Gusti Ayu Komang; Astawa, Ida Nyoman; Wiyasa, I Ketut; Dewi, Nyoman Diah Utari (Jurnal Abdimas Multidisiplin, 2023)
Purpose: This community service aims to help develop Penglukatan Pancoran Solas Pura Taman Mumbul tourism to become an international spiritual tourism destination. Field data collection through observation, interviews and document study. Methodology: The analysis was carried out descriptively, analyzing the 4A components (Attraction, Accessibility, Amenities, Ancillary) and analysis SWOT (Strength, Weakness, Opportunities,Threats). Results: Based on the analysis in the field, the results obtained are that theologically the Pancoran Solas Taman Mumbul in Sangeh has eleven showers where each shower is a symbol of strength God Nawasanga guarding the nine directions of the compass. Therapeutically, painting Pancoran Solas is believed to be able to increase spiritual vibrations and neutralize negative forces in the human body. Based on explanation regarding the 4A component of Penglukatan Pancoran Solas Taman Mumbul Sangeh, the tourism potentials in Penglukatan Pancoran Solas Taman Mumbul Sangeh must be further developed. Seeing that marketing / promotion efforts have not been maximized, then the hope/impact obtained in community service is marketing/promoting the existence of Religious Tourism Penglukatan Pancoran Solas Taman Mumbul Sangeh through social media, thereby increasing the number of tourist visit. The existence of Pancoran Solas Taman Mumbul is a potential for religious tourism which is expected to help improve the economy of the surrounding community and support the development of tourism in Bali. Community participation is very important in managing the existing potential and maintaining the sanctity and sustainability of the Pancoran Solas Taman Mumbul melukat.